1999
DOI: 10.1046/j.1537-2995.1999.39101051.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and visible light spectrophotometric approach to blood typing: objective analysis by agglutination index

Abstract: The method accurately predicted A, B, and O blood groups, and D type in over 275 samples. Scattering theory-based calculations of relative volumes of red cells before and after agglutination show a direct correlation with the agglutination index and provide the theoretical basis of the analysis. This quantitative technique is reproducible and has the potential for automation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…This change is quantified by the AI, which is numerically related to the slope of the spectra in the region of 600 to 1000 nm. Our previous work 6 had shown that AIs above an empirical threshold value of 17 consistently indicated type‐specific antibody reaction and that larger values of AI indicated greater antibody induced agglutination. The large AI in the case of blood group A in the presence of anti‐A (AI = 54.7) and the low AI in the presence of anti‐B (AI = –3.4) demonstrates that the method is effective even when applied to whole blood samples (Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…This change is quantified by the AI, which is numerically related to the slope of the spectra in the region of 600 to 1000 nm. Our previous work 6 had shown that AIs above an empirical threshold value of 17 consistently indicated type‐specific antibody reaction and that larger values of AI indicated greater antibody induced agglutination. The large AI in the case of blood group A in the presence of anti‐A (AI = 54.7) and the low AI in the presence of anti‐B (AI = –3.4) demonstrates that the method is effective even when applied to whole blood samples (Table 1).…”
Section: Resultsmentioning
confidence: 95%
“…The plasma background was automatically subtracted from the test sample spectrum by the instrument. Note that the proportion of plasma has been increased from our originally reported procedure 6 (from equal proportions of plasma and reagent RBCs to three parts to one part, respectively).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, an ultraviolet (UV) and visible light spectrophotometric approach for objectively quantifying red blood cell agglutination has been proposed (Narayanan et al 1999(Narayanan et al , 2002. In this method, blood groups and types are determined by comparing the optical density spectra obtained between 665 and 1,000 nm.…”
Section: Introductionmentioning
confidence: 99%